The Effectiveness of Accounting Information Systems at Hotel Resorts in Ubud - Putu Kepramareni; Ida Ayu Nyoman Yuliastuti; I Wayan Satria Dharma Putra (Advances in Global Economics and Business Journal, 2020)
This study aims to examine and describe the effect of information technology sophistication, accounting, and work experience on accounting information system effectiveness of hotel resort in Ubud. This research paper used purposive sampling method to determine the 152-samples. The research problems were examined by multiple linear regression analysis. The tests revealed that sophistication of information technology, accounting understanding, and work experience positively affect the effectiveness of accounting information systems. This finding could make a valuable contribution to the application of accounting information systems in companies, particularly hotels.